A Gap in Care? Postpartum Women Presenting to the Emergency Room and Getting Readmitted - Patel, Shivani; Rodriguez, Aldeboran N.; Macias, Devin A.; Morgan, Jamie; Kraus, Alexandria; Spong, Catherine Y. (American Journal of Perinatology, 2020)
Objective Emergent postpartum hospital encounters in the first 42 days after birth are estimated to complicate 5 to 12% of births. Approximately 2% of these visits result in admission. Data on emergent visits and admissions are critically needed to address the current maternal morbidity crisis. Our objective is to characterize trends in emergent postpartum hospital encounters and readmissions through chief complaints and admission diagnoses over a 4.5-year period.Study Design All postpartum hospital encounters within 42 days of delivery at our institution from 2015 to 2019 were included. We reviewed demographic information, antepartum, intrapartum, and postpartum care and postpartum hospital encounters. Trends in hospital presentation and admission over the study period were analyzed. Comparisons between women who were admitted to those managed outpatient were performed. Statistical analysis included Chi-square, student's t-test, and Mantel–Haenszel test for trend and ANOVA, as appropriate. A p-value <0.05 considered significant.Results Among 8,589 deliveries, 491 (5.7%) presented emergently to the hospital within 42 days of delivery, resulting in 576 hospital encounters. From 2015 to 2019, annual rates of presentation were stable, ranging from 5.0 to 6.4% (p = 0.09). Of the 576 hospital encounters, 224 (38.9%) resulted in an admission with increasing rates from 2.0% in 2015 to 3.4% in 2019 (p = 0.005). Primiparous women with higher body mass index, cesarean delivery, and blood loss ≥1, 000 mL during delivery were significantly more likely to be admitted to the hospital. Women with psychiatric illnesses increasingly utilized the emergency room in the postpartum period (6.7–17.2%, p = 0.03). The most common presenting complaints were fever, abdominal pain, headache, vaginal bleeding, wound concerns, and high blood pressure. Admitting diagnoses were predominantly hypertensive disorder (22.9%), wound complications (12.8%), endometritis (9.6%), headache (6.9%), and delayed postpartum hemorrhage (5.6%).Conclusion The average proportion of women presenting for an emergent hospital encounter in the immediate 42-day postpartum period is 5.7%. Nearly 40% of emergent hospital encounters resulted in admission and the rate increased from to 2.0 to 3.4% over the study period. The most common reasons for presentation were fever, abdominal pain, headache, vaginal bleeding, wound concerns, and hypertension. Hypertension, wound complications, and endometritis accounted for the top three admission diagnoses.
Keywords: postpartum; emergency room; headache; hypertension; infection